Mathematical model of the visible range optical radiation passing through a water-milk solution - Kucheruk, V.; Kurytnik, I.P.; Kulakov, P.; Vasilevskyi, A.N.; Karabekova, D.Zh.; Mostovyi, D.; Kulakova, A. (KSU Publ., 2018)
A mathematical model and a mathematical modeling of the passing visible range optical radiation through a water-milk solution are carried out. The mathematical model was created on the basis of theoretical and experimental studies of the spectral characteristics of water-milk solution passing. As a result of the modeling, the dependence of the output voltage of the linear photoreceiver, which based on a pair of photodiodeoperating amplifier from the relative mass fraction of milk in the water-milk solution and the wavelength of the optical radiation in the visible range is obtained. The optimal wavelength of infrared radiation was determined by determining the maximum of the ratio of the spectral characteristics of water and milk. The question of passing the visible range optical radiation through the water-milk solution has not been studied at the present time, which determines the relevance of these studies.
Су-сүтті ерітінді арқылы көрінетін ауқымдағы оптикалық сəулелену өтуінің математикалық моделі
Математическая модель прохождения оптического излучения видимого диапазона через водно-молочный раствор
Keywords: water-milk solution; visible range; optical radiation passing; detection of water in milk